Frontiers of the Roman Empire = Frontières de l'Empire Romain - Breeze, David J. (Archaeopress Archaeology, 2022)
This volume considers the military architecture and its impact on local communities in Rome's eastern frontier, which stretched from the north-east shore of the Black Sea to the Red Sea.